PENGARUH SEMANGAT KERJA PEGAWAI PADA KANTOR CAMAT SAMARINDA UTARA TERHADAP PRODUKTIVITAS KERJA ( PENGURUSAN DOKUMEN ) - ., Pambudiningsih (PREDIKSI, 2012)
Each unit of work will always try to fully engage its human resources in order to produce a high work productivity and achieve the goals set. Head Office North Samarinda is a unit of work that serves communities in North Samarinda . The purpose of this study was to obtain information about the motivation and productivity of employees working in North Samarinda Head Office, as well as to determine how much influence the motivation to work on the productivity of employees working in North Samarinda Head Office and whether there is a strong relationship between motivation and productivity of work .